Pyomyoma uterus: a case report - Jose, Clerin; Alex, Anju; Dettin, Annie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pyomyoma of uterus is rare usually misdiagnosed as degeneration of fibroid. Delay in diagnosis can lead to significant increase morbidity and mortality. Here we present a case of 34-year-old woman presented with complaints of lower abdominal pain, low backache, and gradually developed fever, which progressed to sepsis. Clinical evaluation and imaging revealed a large uterine fibroid with infarction. She was treated with intravenous antibiotics and required blood transfusions. Since her condition worsened, planned for hysterectomy. She became asymptomatic after surgery. This case emphasized the importance of considering pyomyoma in the differential diagnosis of sepsis in women with uterine fibroids, especially when there is pain and sepsis.